ON THE REALIZATION OF HIGH PERFORMANCE CURRENT CONVEYORS AND THEIR APPLICATIONS - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2013)
In this work, a wideband and high-performance CMOS implementation of 2nd-generation current conveyor (CCII) is proposed. The proposed circuit is composed of a high performance voltage follower stage which is based on differential pairs to provide high voltage swings on input and output ports and a current follower stage. It is shown that the proposed voltage follower stage can be used to implement high performance 1st and 3rd-generation current conveyors (CCI and CCIII, respectively) that have very small equivalent impedances on ports X, high equivalent impedances on ports Y and Z and also high-valued voltage and current transfer bandwidths. 2nd and 3rd order filter circuits as well as a half-wave recti filer circuit are given to show the performance and usefulness of the proposed current conveyor circuits. The simulation and experimental results are given to verify the theoretical analyses.
Keywords: Current-mode circuits; second-generation current conveyor; CCII; Butterworth filter; FILTERS